Exploring Overall Equipment Efficiency Model of Laboratory Capital Equipments in Malaysian Public Universities - Abdul Majid, Izaidin; Ngadiman , Yunos; Hussin, B. (2011)
Overall Equipment Effectiveness (OEE) began to be recognized as a fundamental method for measuring plant performance in the late 1980s and early 1990s. It was a period that saw the emergence of serious big company maintenance benchmarking, the introduction of Total Productive Maintenance (TPM) in United State of America and the founding of the Society for Maintenance Reliability Professionals. At first, OEE was closely bound to TPM and often was seen as a defining measurement for winning the TPM Prize. Recognizing OEE as an effective productivity management metric is one thing, using it effectively is another, as many practitioners have found out. In this research, accurately survived to develop a practical how to approach to using OEE which lays out in Overall Equipment Effectiveness to Overall Equipment Efficiency (OEE) whereas participating of quality performance and organizational management elements could be involved in creating an integration measurement model of OEE for identify the performance efficiency of the high capital equipment purchased in public universities in Malaysia. The methodologies of this research will be proposed to conducting interviews with the experienced respondents among department head, instructor, lecturer and technicians in public universities, searching the related topic literatures, white papers, technical papers, conference proceedings, web pages or even communicate to the personnel in selected public universities in Malaysia. The potential research finding is to develop a new OEE measurement model of laboratory capital equipment in public universities towards proper managing the technology of capital equipment consist utilization, performance and quality management.